Compositional analysis of mole cricket (Gryllotalpa orientalis Burmeister) I. proximate and fatty acid composition - Zamora, Rosally Padilla; Dumelod, Benelyn Domingo (2000.)
The proximate and fatty acid composition of raw, preprocessed and cooked mole cricket (Gryllotalpa orientalis Burmeister) were determined. The moisture content was analyzed using the air oven method; crude fat content was determined using the Bligh and Dyer method; crude protein level was assessed using the Kjeldahl method; total carbohydrate available was ascertained using the Clegg anthrone method; and the ash content analysis was made possible through subjection of the samples at 500°C. The fatty acid distribution was analyzed by gas chromatography. The moisture, fat, protein and total carbohydrate contents of the raw mole cricket significantly changed by preprocessing and cooking, while the ash levels of the three treatment were not significantly different from each other. The decrease in the amount of moisture due to the drying action of frying caused the concentration of the constituents in the cooked sample. Out of 11 fatty acids identified, palmitic, oleic and linoleic are the most predominant in the raw and the preprocessed samples, whereas lauric and oleic predominated the cooked sample. This may be attributed to the fatty acids absorbed from the cooking medium. Four eluents were not identified. Based on their retention times, it is possible that components A, B and C are unsaturated analogs of palmitic acid, while component D is either an unsaturated analog of arachidic or docosanoic acid. Appreciable amounts of linoleic and linolenic acids were found in the preprocessed samples and these are essential precursors of eicosanoids, which are responsible for the maintenance of homeostasis in the body.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mole crickets -- Analysis